Development of Kiln-Drying Schedules for Two Lesser-Known Timber Species in Ghana - Effah, Bernard; Effah, Bernard (Journal of Science and Technology, 2014)
Abstract Cola nitida and Funtumia elastica are two lesser- known species in Ghana that are not used for commercial timber purposes. The objective of this study was to develop kiln-drying schedules for Cola nitida and Funtumia elastica as the basis for determining the potential uses that may encourage the utilization and promotion of these lesser known species. The drying schedules were determined using the quick drying test method developed by Terazawa (1965). Three trees each per species were used in the study. The drying schedules comformed to those of Sterculia rhinopetala and Alstonia boonei. Checks in the early stages of drying were less severe in both Cola nitida and Funtumia elastica samples (Class 3). There were no honeycombing (Class 1) in both Cola nitida and Funtumia elastica species. There was no deformation (Class 1) in both Cola nitida and Funtumia elastica species. Experimental dry kiln schedules for lumber of thickness up to 38 mm corresponding to two Madison schedules were proposed: Cola nitida (T10-C4) and Funtumia elastica (T10 – D4).